A Randomized Trial of Individual and Couple Behavioral Alcohol Treatment for Women - McCrady, Barbara S. (2009)
Although alcohol use disorders (AUDs) adversely affect women, research on efficacious treatments for women is limited. In this randomized efficacy trial of 102 heterosexual women with AUDs, the authors compared alcohol behavioral couple therapy (ABCT) and alcohol behavioral individual therapy (ABIT) on percentage of days abstinent (PDA) and percentage of days of heavy drinking (PDH) over 6 months of treatment and 12 months of posttreatment follow-up. Baseline relationship functioning and comorbid disorders were tested as moderators of outcome. Piecewise linear growth models were used to model outcomes. During treatment, women increased their PDA and decreased their PDH, with significantly greater improvements in ABCT than in ABIT (d = 0.59 for PDA; d = 0.79 for PDH). Differences favoring ABCT were maintained during follow-up. Women with poorer baseline relationship functioning improved more on PDA during treatment with ABCT than with ABIT. For PDH, results during treatment and follow-up favored ABCT for women with better baseline relationship functioning. ABCT resulted in better outcomes than ABIT for women with Axis I disorders at the end of follow-up (PDA), and for women with Axis II disorders at the end of treatment (PDA) and at the end of follow-up (PDH).